Beneficial endophytic fungi improve the yield and quality of Salvia miltiorrhiza by performing different ecological functions - Li,Xiaoyu; Lin,Yali; Qin,Yong; Han,Guiqi; Wang,Hai; Yan,Zhuyun (PeerJ, 2024)
Background Endophytic fungi can enhance the growth and synthesis of secondary metabolites in medicinal plants. Salvia miltiorrhiza Bunge is frequently employed for treating cardiovascular and cerebrovascular ailments, with the primary bioactive components being salvianolic acid and tanshinone. However, their levels in cultivated S. miltiorrhiza are inferior to that of the wild herbs, so the production of high-quality medicinal herbs is sharply declining. Consequently, the utilization of beneficial endophytic fungi to improve the yield and quality of S. miltiorrhiza holds great significance for the cultivation of medicinal plants. Methods In this study, nine non-pathogenic, endophytic fungal strains were introduced into sterile S. miltiorrhiza seedlings and cultivated both in vitro and in situ (the greenhouse). The effects of these strains on the growth indices, C and N metabolism, antioxidant activity, photosynthesis, and content of bioactive ingredients in S. miltiorrhiza were then evaluated. Results The results showed that the different genera, species, or strains of endophytic fungi regulated the growth and metabolism of S. miltiorrhiza in unique ways. These endophytic fungi primarily exerted their growth-promoting effects by increasing the net photosynthetic rate, intercellular CO2 concentration, and the activities of sucrose synthase, sucrose phosphate synthase, nitrate reductase, and glutamine synthetase. They also enhanced the adaptability and resistance to environmental stresses by improving the synthesis of osmoregulatory compounds and the activity of antioxidant enzymes. However, their regulatory effects on the growth and development of S. miltiorrhiza were affected by environmental changes. Moreover, the strains that significantly promoted the synthesis and accumulation of phenolic acids inhibited the accumulation of tanshinones components, and vice versa. The endophytic fungal strains Penicillium meloforme DS8, Berkeleyomyces basicola DS10, and Acremonium sclerotigenum DS12 enhanced the bioaccumulation of tanshinones. Fusarium solani DS16 elevated the rosmarinic acid content and yields in S. miltiorrhiza. The strain Penicillium javanicum DS5 improved the contents of dihydrotanshinone, salvianolic acid B, and rosmarinic acid. The strains P. meloforme DS8 and B. basicola DS10 improved resistance. Conclusion Various endophytic fungi affected the quality and yield of S. miltiorrhiza by regulating different physiological and metabolic pathways. This study also provides a novel and effective method to maximize the effects of beneficial endophytic fungi by selecting specific strains to design microbial communities based on the different ecological functions of endophytic fungi under varying environments and for specific production goals.
Keywords: Salvia miltiorrhiza; Endophytic fungi; Secondary metabolite; Medicinal plant; Plant-microbe interactions; Ecological functions; Photosynthesis